Słabo rozwinięta kompetencja leksykalna dorosłych – przyczyny, skutki i możliwości jej poprawy - Targońska, Joanna (Neofilolog, 2019)
The present paper attempts to investigate causes of poor lexical compe-tence of prospective students of modern philology. The focus is placed on the techniques and cognitive strategies selected by such students in learning lexis.